LITERATUR REVIEW : PENERAPAN TEKNIK RELAKSASI GENGGAM JARI DALAM MENGURANGI INTENSITAS NYERI PADA KLIEN POST APPENDIKTOMY - Ahmad Muzaki, Basuki Widiyanto, Wahyu Eko Yuliana (AKPER Pemkab Purworejo, 2021)
Appendicitis is inflammation of vermiformis. In mild cases it can be cured without treatment, but many cases require a laparotomy by removing the tufts of infected worm tuft. Appendicitis post operative patien often experience pain due to a surgical incision. Finger-handed relaxtion is a non-pharmacological technique to reduce pain. Objective : this study was to determine the effect of hand-held relaxation on pain reduction in post operative appendicitis patients. Method : the research used in this study is a literature review on hand-held relaxation techniques. Searching for articles is carried out with Goggle Search and ProQuest from 2016 to 2020, accessed fulltext in pdf format. Result : there is an effect of the relaxation of the finger grip on pain reduction in post op appendectomy patients. Conclusion : the level of pain before being given a hand-held relaxation is in the category of moderate pain, and after being given a mild pain category. Significantly demonstrated that the hand-held relaxation techniques is an effective techniques in reducing pain intensity.